Ecotourism model with travel cost approach: A case study on Air Manis Beach - Idris Idris (Jurnal Kajian Manajemen Bisnis, 2022)
Indonesia has coastal nature tourism potential (ecotourism). However, the potential of marine tourism in Indonesia is still not optimally utilized. For this reason, a study is needed to conduct an economic valuation of Air Manis Beach ecotourism as a basis for the development of this area in the future. By using a survey, this study aims to get perceptions and opinions of the utility or tourist satisfaction of various aspects of service, such as facilities and infrastructure, cleanliness, security, and attractions. This study also to seek the ability to pay of air manis beach by using Contingent Valuation Method (CVM). The results of the inductive analysis using the travel cost method found that travel costs, income, gender and young age have a significant effect on determining the number of tourist visits. In terms of willingness to pay, more respondents stated that the price of admission during the survey (IDR. 5,000) was moderate. Based on the market hypothesis, respondents who agree to the additional price of admission to improve services and infrastructure in the Air Manis Beach tourist attraction area are 58.3 percent of respondents, while those who disagree are 41.7 percent. The total additional increase that is willing to be paid is IDR. 498,000 or an average of IDR. 2,767 per each respondent.